PENGARUH PEMBERIAN GIBERELIN PADA PERTUMBUHAN RUMPUN PADI IR-64 (Oryza sativa var IR-64) - Parman, Sarjana (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
The research objective was to determine the effect of administration of Gibberellins on Growth pembeian clump IR-64 rice (Oryza sativa var IR = 64). This research laboratory dilakkan BSFT MIPA UNDIP FSM.Ilanjukan with the effect of giving gibberellin on growth of the IR-64 rice (Oryza sativa IR-64 with RAL design is done in the fields pwercobaan, one treatment that is giving giberelinie 0 mg / l; 5 mg / l; 10 mg / l; 15 mg / l; and 20 mg / l. given crop spraying since the age of 7 HST, repeated every 7 days with giberelin volume, 500 ML / ha, which dilajutkan the Duncans test 5%. The results showed there were differences in plant height of rice to week -7 though there are similarities in the pattern of increase in plant height spraying all treatments are the same. The number of grains and grain on the contents of the treatment penyemprotngiberelin 5 mg / l - 15 mg / l in contrast to the control, was treated spraying gibberellin 20 mg / l is not significantly different. Giving gibberellin concentrate 10 mb / l was able to increase the number of tillers per hill that formed start week 4 to week 8.. gibberellin concentration of 10 mg / l is the optimum concentration where the height of rice plants at week 23 reached average -rata 56.91 (50.22 cm control; the establishment of rice seedlings per hill at week 8 was 34.89 tillers per hill, control tiller 29.07 every clump. Â Keywords: gibrelin, clumps of rice IR-64Â , the number of tillers per hill, plant height